GUIDANCE AND COUNSELING TEACHERS’ ASSESSMENT LITERACY: A KEY TO IMPROVING THE ACCURACY OF STUDENT PROBLEM IDENTIFICATION - Dianti, Tiara Maiza (Program Studi Bimbingan dan Konseling FKIP UNJA, 2025)
This study aims to analyze the role of assessment literacy among Guidance and Counseling (GC) teachers in improving the accuracy of student problem identification. Assessment literacy includes teachers’ ability to understand, select, apply, and interpret various assessment instruments, both test and non-test. This research employed a Systematic Literature Review (SLR) method by analyzing 12 nationally accredited journal articles published between 2020 and 2025. The findings indicate that assessment literacy significantly contributes to the accuracy of GC teachers in identifying students’ needs and problems. Low assessment literacy often leads to misdiagnosis and ineffective counseling services, while training and the use of digital technology have proven to enhance assessment accuracy. The study implies the importance of strengthening teachers’ assessment competencies through continuous professional development and technology integration. The originality of this research lies in its systematic synthesis of recent studies on GC teachers’ assessment literacy in Indonesia.